The Impact of a Peer Support Program on the Social and Emotional Wellbeing of Postgraduate Health Students During COVID-19: A Qualitative Study - Jinal Shashin Parmar; Poshan Thapa; Sowbhagya Micheal; Tinashe Dune; David Lim; Stewart Alford; Sabuj Kanti Mistry; Amit Arora (Education Sciences)
Peer support is a widely adopted strategy in higher education, facilitating student engagement in socially safe groups to enhance knowledge and social skills. While its benefits are recognized during in-person education, evidence supporting these benefits in an online format of study, especially among postgraduate health students, remains scarce. This study explored the impact of a peersupport program on the social and emotional well-being of postgraduate health students who were studying online during the COVID-19 pandemic. Peer support groups were implemented for a mixed group of local and international students enrolled in a postgraduate health subject delivered online in 2021 at Western Sydney University, Australia. Data were collected using four focus group discussions conducted via Zoom, transcribed verbatim, translated (as required), and analyzed through inductive thematic analysis. Three major themes were identified: (i) emotional well-being and social support; (ii) social interactions and forming friendships; and (iii) facilitators and barriers to engagement. This study highlights the positive impact of the peer support program in enhancing social and emotional well-being among post-graduate health students, with most being international students. Despite the challenges posed by online learning during COVID-19, students experienced significant social, emotional, and cultural benefits from participating in the peer support program.